Collaborative society - Jemielniak, Dariusz; Przegalinska, Aleksandra (Cambridge : The MIT Press, 2020)
How networked technology enables the emergence of a new collaborative society. Humans are hard-wired for collaboration, and new technologies of communication act as a super-amplifier of our natural collaborative mindset. This volume in the MIT Press Essential Knowledge series examines the emergence of a new kind of social collaboration enabled by networked technologies. This new collaborative society might be characterized as a series of services and startups that enable peer-to-peer exchanges and interactions though technology. Some believe that the economic aspects of the new collaboration have the potential to make society more equitable; others see collaborative communities based on sharing as a cover for social injustice and user exploitation. The book covers the "sharing economy," and the hijacking of the term by corporations; different models of peer production, and motivations to participate; collaborative media production and consumption, the definitions of "amateur" and "professional," and the power of memes; hactivism and social movements, including Anonymous and anti-ACTA protest; collaborative knowledge creation, including citizen science; collaborative self-tracking; and internet-mediated social relations, as seen in the use of Instagram, Snapchat, and Tinder. Finally, the book considers the future of these collaborative tendencies and the disruptions caused by fake news, bots, and other challenges.
OCLC-licensed vendor bibliographic record.
Keywords: elektronické knihy; electronic books; Online social networks; Social networks; Cooperation